Development of Evaluation-Based Role Playing Methods in Civics Subjects in Improving the Character of Nationalism - Safitri Kirana Giyono; Rosalia Indriyati Saptatiningsih (Universitas of Muhammadiyah Makassar, 2023)
This study aims to determine (1) the development of an evaluation-based role-playing method in Civics subjects in enhancing the character of nationalism and (2) the feasibility of the evaluation role-playing method as a learning method in increasing the character of nationalism at Junior High School of 15 Yogyakarta. The research method refers to the Dick and Carry model, which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The research was conducted at VIII A at Junior High School of 15 Yogyakarta, Lempuyangan Road, number 61, Yogyakarta. The number of respondents was 32 students. Data collection techniques using observation, interviews, documentation, and questionnaires. Data analysis uses the Likert scale to test and produce the feasibility percentage of the evaluation based on the role-playing method. The conclusions from the research results of this study are (1) the development of an evaluation-based role-playing method in civics subjects to enhance the character of nationalism at Junior High School of 15 Yogyakarta with the ADDIE model. The analysis stage is carried out by observing in class; the next step is designed by creating learning methods, lesson plans, and evaluations based on dialogue content. The research continued with the development stage, namely product creation and the validation process by two validators. Next is implementing an evaluation-based role-playing learning method, ending with an evaluation. The results of the student questionnaire evaluation were 87.93%; and (2) the evaluation-based role-playing process is categorized as feasible based on the results of the learning method validator by 100%, lesson plans by 96.25%, and evaluation-based role-playing dialogue content by 95%.